2005
DOI: 10.1016/j.biopsych.2004.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral heterogeneity in an animal model of neuropsychiatric lupus

Abstract: Background-Various psychiatric manifestations of unknown etiology are common in systemic autoimmune disease lupus erythematosus (SLE). Profound heterogeneity at clinical and neuropathological levels suggests distinct subpopulations of SLE patients and multiple mechanisms in the pathogenesis of aberrant behavior. Using inbred mice prone to SLE-like condition, we presently examine whether subpopulations of diseased mice can be identified on the basis of their behavioral performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 78 publications
3
28
0
Order By: Relevance
“…Since onset of serological and peripheral manifestations differs among littermates, dissimilar timing in loss of central dopaminergic neurons may contribute to behavioral heterogeneity and proclivity to SIB in the inbred MRL-lpr substrain. 43 In summary, one may hypothesize that diverse behavioral deficits in MRL-lpr mice are result of complex genetic and perinatal autoimmune mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Since onset of serological and peripheral manifestations differs among littermates, dissimilar timing in loss of central dopaminergic neurons may contribute to behavioral heterogeneity and proclivity to SIB in the inbred MRL-lpr substrain. 43 In summary, one may hypothesize that diverse behavioral deficits in MRL-lpr mice are result of complex genetic and perinatal autoimmune mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The MRL-lpr strain, however, has no gender bias, possibly suggesting a different hormonal differentiation between two sexes in human and murine lupus. Lastly, while more sophisticated and systematic assessments are administered in human SLE, affective states of MRL-lpr mice can only be assessed by behavioral tests (Scolding and Joseph, 2002;Sakic et al, 2005a), and care is required when transferring information obtained from an animal model to human disease. Despite these limitations, the MRL model of NP-SLE remains a critical tool toward understanding the complex etiopathogenesis of this neuroimmunological syndrome.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The observed behavioral changes are not completely dependent on the systemic pathology, since we observed behavioral alterations in these mice from 5 wk of age (data not shown), at which point they are clinically normal. Furthermore, others have reported that these mice showed heightened emotional reactivity and displayed increased anxiety and decreased exploratory behavior at an age when they are free of clinical symptoms, which could impair their ability to perform behavioral tasks [55]. These behavioral alterations could also be cytokine driven, since deposition of immune complexes could lead to changes in cytokine profiles [56].…”
Section: Behavioral Changes In Mrl/lpr Mice Are Complement Dependentmentioning
confidence: 99%